Role on Moment of Inertia and Vortex Dynamics for a Thin Rotating Plate - Kubota, Yoshihiro; Mochizuki, Osamu (My University, 2013)
In this study, we focused on the lift generation with a thin rotating plate. The objective of this study is to understand the appropriate shape and the role of vortex for rotating thin plate. We determined the shape of the plate through free-flight tests of paper strips and investigated the aerodynamic characteristics of the rotating plate with the selected shape. The rectangular plate with an aspect ratio 7 was relevant from moment of inertia and bending stress. An endplate on a wing tip increased the stability on the lateral vortex structure behind the rotating plate. Velocity field measurement by Particle Image Velocimetry (PIV) showed that the lift force was generated twice in a rotating cycle
Keywords: Autorotation; Thin Rotating Plate; Free Flight; Moment of Inertia; Visualization; PIV